Fabrication of Cr2AlC coating from a cost-efficient Cr–Al–C target by arc ion plating. Issue 1 (5th November 2018) - Li, Yueming; Zhao, Guorui; Du, Beining; Li, Meishuan; Xu, Jingjun; Qian, Yuhai; Sheng, Liyuan; Zheng, Yufeng
Abstract : In the present research, a novel cost-efficient chromium (Cr)–aluminum (Al)–carbon (C) target hot-pressed at 650°C with chromium:aluminum:carbon = 2:1:1 (molar ratio) was applied to fabricate chromium aluminum carbide (Cr2 AlC) coatings by the arc ion plating method at room temperature and subsequent annealing. Scanning electron microscopy, X-ray diffraction and transmission electron microscopy were used to characterize the coatings and the target. The results showed that the chromium–aluminum–carbon target mainly comprised chromium, carbon and chromium aluminum compound (Cr9 Al17 ). By arc ion plating with the hot-pressed chromium–aluminum–carbon target and subsequent annealing at 620°C, polycrystalline chromium aluminum carbide coating with minor chromium carbide (Cr3 C2 ) was obtained. The as-prepared chromium aluminum carbide coating was dense and crack-free, and there existed macroparticles in the coating. Transmission electron microscopy observations revealed that the as-prepared chromium aluminum carbide coating exhibited a multilayer structure vertical to the growth direction. The coating possessed hardness and adhesion strength of 8·8 ± 0·8 GPa and 42 ± 17 MPa, respectively, which could meet the basic requirement of high-temperature protective coating.